(untitled) (Nigerian Journal of Physiological Sciences, 2025)
Medical education increasingly emphasizes active learning strategies to enhance engagement, understanding, and higher-order cognitive skills. Model-making competitions represent a creative, student-centered approach that encourages conceptual clarity, innovation, and teamwork in physiology education. This study aimed to explore undergraduate medical students’ perceptions of model-making competitions as an active learning strategy in physiology, focusing on conceptual understanding, creativity, and teamwork. A model-making competition was organized for 150 first-year MBBS students, divided into 30 self-formed teams. Each team prepared a model on a physiology topic of their choice over one month, with faculty guidance available as needed. Completed models were exhibited and evaluated by senior faculty using a structured rubric. Following the event, students completed a structured feedback questionnaire to assess their perceptions of the activity. Of 150 participants, 128 (85.3%) provided feedback. The overall experience was rated Excellent (53.9%) or Good (44.5%). A majority (97%) reported improved conceptual understanding, while 95% agreed the activity fostered creativity. Teamwork was rated Excellent by 50% and Good by 39%. Most students (95%) felt preparation time was adequate, 69% expressed willingness to participate again, and 90% reported being motivated to explore physiology concepts further. Model-making competitions were perceived as highly effective in enhancing conceptual understanding, fostering creativity, and promoting teamwork. These findings support the integration of model-making into the physiology curriculum as an engaging and practical student-centered teaching–learning strategy. •